Digitale Kardiologie - Meder, Benjamin; Radke, Peter W. (Deutsche medizinische Wochenschrift, 2019)
The increase in life expectancy and Healthy Life Years in Europe is largely attributable to the success of cardiovascular medicine. Technical developments enable ever more detailed insights into disease processes and enable a precise, multimodal diagnosis of even complex diseases using digital imaging, cardiac biomarkers and genomic information. The rapid availability of this data, often in real time, allows optimized planning and performing of tailored interventional, surgical, or pharmacotherapies. But there are also completely new challenges due to the growing flood of data, the integration of which can no longer be achieved by the individual doctor. The active involvement and participation of the patient also requires new digital concepts and should include decision-making, treatment planning, (long-term) history, and feedback on success and adverse drug reactions. By using artificial intelligence, digital communication and decision support systems, economic benefits, quality improvements and acceleration of outpatient and inpatient treatment become possible. The DGK supports these developments in its own activities, both in project planning, communication with specialist groups, and in training and education. In this article you will find excerpts from current developments of digital cardiology.